Resolution of allergic bronchopulmonary aspergillosis preceded by allergic fungal rhinosinusitis, without glucocorticoid therapy in an immunocompetent individual: a case report with narrative literature review - Dev, Prasanth P.; Varghese, Jophy; Kompithra, Rajeev Z.; K., Sudeep; Joseph, George; Abraham, Joison (International Journal of Research in Medical Sciences, 2025)
Allergic bronchopulmonary aspergillosis (ABPA), seen predominantly in patients with uncontrolled bronchial asthma, cystic fibrosis, and immunocompromised patients, can uncommonly occur in an immunocompetent host. Rarely, an ABPA patient can have a preceding or concomitant history of its upper respiratory counterpart, allergic fungal rhinosinusitis (AFRS). The traditional mainstay of ABPA treatment is systemic glucocorticoids. We report a case of ABPA in a woman with a history of AFRS and recurrent atopic rhinitis, but with no previous definitive history of bronchial asthma or cystic fibrosis, that resolved without systemic glucocorticoid therapy. A 52-year-old female patient, a non-smoker, previously operated for AFRS, presented to the outpatient department with fever with chills, right-sided pleuritic type of chest pain, and cough with brown-black expectoration. The absolute eosinophil count was 1360. Serum baseline IgE was >2500. A chest X-ray revealed consolidation in the right middle zone. High-resolution computed tomography (HRCT) of the thorax revealed linear branching hyperdense content in a few of the dilated bronchi. Fiber-optic bronchoscopy confirmed thick mucus plugging at the lateral segment of the right middle lobe, pathognomonic of ABPA with high-attenuation mucus (ABPA-HAM). Oral Itraconazole monotherapy 200 mg twice daily for one day, followed by 100 mg twice daily for a total period of four months’ duration, had no significant adverse events during treatment. C-reactive protein decreased significantly by 2 weeks, total serum IgE levels by 2 months; and repeat chest X-ray at 6 months showed complete resolution of pulmonary infiltrates. This case report corroborates recent revised 2024 ISHAM-ABPA working group guidelines advocating Itraconazole monotherapy alone for treating acute ABPA.